Single-pump multiwavelength hybrid raman-EDF laser using a non-adiabatic microfiber interferometer - Muhammad Faiz Ibrahim; Nani Fadzlina Naim; Mas Izyani Bt Md Ali (Institute of Advanced Engineering and Science, 2020)
This paper presents a multiwavelength fiber laser utilizing non-adiabatic tapered EDF based Mach Zehnder Interferometer (MZI) in hybrid Raman-EDF gains design with a linear cavity. A stable laser was obtained from the single pump with a 1497 nm wavelength through the employment of a 20:80 optical circulators and 99% reflective mirror. The generated backward propagating oscillates inside the laser cavity generate the stable multiwavelength output with 4 channels, which is coupled out via the 10:90 coupler and the output laser is characterized using an OSA with a resolution of 0.015 nm. The hybrid Raman-EDF gain is pumped from the external cavity by a Raman Pump Unit (RPU) and produced a stable multiwavelength laser output with SMSR of 28.9 dBm for 300 mW pump power, 30.7 dBm for 1000 mW pump power and 33.7 dBm for 1500 mW pump power.